2016
DOI: 10.1007/s11469-016-9640-z
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Exploration of Community Pharmacists’ Views on the Nature and Management of Over-the-Counter (OTC) and Prescription Codeine Misuse in Three Regulatory Regimes: Ireland, South Africa and the United Kingdom

Abstract: A comparative exploration of community pharmacists' views on the nature and management of Over-the-Counter (OTC) and Prescription codeine misuse in three regulatory regimes; Ireland, South Africa and the United Kingdom. AbstractMisuse of codeine containing preparations is a public health concern given the potential for associated harms and dependence. This study explores the perspectives of community pharmacists in three regulatory regimes on issues of customer misuse of over the counter (OTC) and prescribed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 44 publications
2
20
0
Order By: Relevance
“…In addition, it was reported that when codeine was regulated to Schedule 3, some pharmacists were concerned about their clinical competence not being sufficient to help patients with pain management without the aid of over-the-counter CCPs [24]. It was consistent in most of the studies that the up-scheduling of codeine required additional educational training for pharmacists in the area of pain management, counseling skills, and the handling of drug misuse [13,23,24]. This could imply that, if a change in CMs scheduling were to eventuate, pharmacists, pharmacy assistants, and pharmacy technicians would need to undertake professional training in the area of CMs to build on their evidence-based CMs knowledge.…”
Section: Marketing and Advertisingmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, it was reported that when codeine was regulated to Schedule 3, some pharmacists were concerned about their clinical competence not being sufficient to help patients with pain management without the aid of over-the-counter CCPs [24]. It was consistent in most of the studies that the up-scheduling of codeine required additional educational training for pharmacists in the area of pain management, counseling skills, and the handling of drug misuse [13,23,24]. This could imply that, if a change in CMs scheduling were to eventuate, pharmacists, pharmacy assistants, and pharmacy technicians would need to undertake professional training in the area of CMs to build on their evidence-based CMs knowledge.…”
Section: Marketing and Advertisingmentioning
confidence: 96%
“…Some pharmacists felt that it gave them confidence to discuss with patients any codeine-related problems [25]. Some pharmacists would attempt to address a patient's concerns and recommend alternatives to minimize codeine use [13,23]. Other pharmacists felt that rescheduling to Schedule 3 prompted them to upskill in the area of pain management [23].…”
Section: Marketing and Advertisingmentioning
confidence: 99%
See 1 more Smart Citation
“…How this questioning should precede at the point of sale should be examined in closer detail. A qualitative study of pharmacists working in Ireland found that refusing codeine usually resulted in the product being bought elsewhere (29).…”
Section: Discussionmentioning
confidence: 99%
“…The focus of this study was to complement previous epidemiological research [1] and research on pharmacists [8] and GPs [5] conducted in SA by investigating the perspectives of addiction treatment providers regarding treatment for codeine misuse or dependence. Specific objectives included documenting: (i) the kinds of professionals providing treatment; (ii) the settings in which treatment is provided; (iii) the kinds of interventions delivered; (iv) the reasons patients come to treatment for codeine-related problems; (v) the barriers to their accessing treatment; (vi) the training needs for addiction treatment providers in terms of addressing codeine misuse and dependence; (vii) the best means for receiving additional training, should it be required; and (viii) ways to improve treatment or initiate innovations in this area.…”
Section: Objectivesmentioning
confidence: 99%